Sexually dimorphic response to tobacco in the development of chronic kidney disease: a systematic review - Wu, Nicole; Chow, Ryan; Verhoeff, Natasha; Venkatraman, Aditi; Xiang, Alexander; Fong, Evan; Heid, Olivia; Shorr, Risa; Jama, Sadia; Cowan, Aaron; Pakhale, Smita (Université d'Ottawa | University of Ottawa, 2024)
Abstract Introduction Chronic kidney disease (CKD) demonstrates a complex interaction with tobacco exposure and sex differences, where females and males may experience varying risks and outcomes. This study aims to investigate how sex differences mediate the relationship between tobacco exposure and CKD development, with a secondary focus on regional variability and social determinants of health. Study selection and criteria Comprehensive searches on MEDLINE, EMBASE, clinicaltrials.gov, and MedRxiv until October 6, 2022, were conducted. Eligibility criteria involved any study that reported primary data on the prevalence of CKD, with information pertaining to both sex and tobacco exposure. Data extraction Data retrieved include patient socio-demographic characteristics, general study information, diagnostic methods, social determinants of health, and the cause of CKD (e.g., tobacco-related or non-tobacco-related). Results Studies were selected through a comprehensive search using key terms such as "chronic kidney disease," "smoking," and "sex differences," which identified 3,025 articles, of which 28 were selected for full texts after screening titles, abstracts. Among the 28 included studies, smoking was consistently identified as a significant risk factor for CKD, with notable disparities related to sex, socioeconomic status, race, and urban versus rural settings. Significant geographical variability in CKD prevalence was observed, ranging from 2.5% to 68.1%, with the highest prevalence in Asia. However, due to high heterogeneity and methodological limitations, a meta-analysis of CKD prevalence stratified by sex and tobacco exposure was not feasible. Conclusions The findings emphasize the need for further research to comprehend the intricate relationship between, tobacco exposure, sex, and CKD management, as well as the consideration of cultural, geographical, socioeconomic, political, and structural factors when understanding the pathophysiology and management of CKD.